Vibration trauma as a causative factor of internal carotid artery dissection - Jacek Jaworski; Lidia Kotuła; Dominika Budzisz-Turbakiewicz; Kinga Kądziołka; Katarzyna Grabowska-Aleksandrowicz; Tomasz Blicharski; Janusz Kocki; Konrad Rejdak (Kazimierz Wielki University, 2019)
Vibration trauma serves as a potential yet not recognized in large clinical series risk factor of cervical artery dissection. We present case report of a young male patient who developed internal carotid artery dissection as a result of prolonged drilling.